Impelementasi Istihsan dalam Pengelolaan Harta Wakaf di Luar Ketentuan Wakif : Studi Kasus KUA Kec Somba Opu - munir, misbahul munir; Hamzah Hasan; Patimah (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
This study aims to examine the application of (1) istihsān in the management of waqf assets at the KUA of Somba Opu District, (2) as well as to identify the obstacles and challenges that arise in the management of waqf assets beyond the stipulations of the wakif, (3) the reality of waqf assets managed using istihsān at the KUA of Somba Opu District. The approach used in this study is an empirical juridical approach through documentation studies and interviews with the staff of the KUA of Somba Opu District. This study employs a field research (qualitative field research) approach, with data obtained through in-depth interviews, direct observation, and a review of relevant documents. This research discusses the implementation of istihsān in the management of waqf assets beyond the provisions set by the wakif at the KUA of Somba Opu District. The results of the study indicate that (1) istihsān provides a reasoning framework that allows waqf management to be carried out more adaptively, particularly in responding to the evolving needs of the community. (2) This study finds that the application of istihsān is inseparable from several constraints. Concerns arise regarding the potential shift from the original intention of the wakif if the flexibility of legal determination is not accompanied by strict supervision standards. Meanwhile, practical obstacles appear in the limited capacity of nazir to understand and interpret considerations of public benefit objectively, as well as the low level of public literacy regarding waqf. (3) Empirical findings at the KUA of Somba Opu District regarding the reality of waqf assets show that the application of istihsān in waqf management has been carried out in accordance with the governance principles recommended by BWI. This practice aligns with the values of maqāṣid al-syarī‘ah. This study is expected to provide theoretical and practical contributions in understanding istihsan as a method used in the management of waqf assets so that it continues to bring sustainable benefits, and can serve as a reference for students, researchers, and other academics. Keywords : Istihsan, Waqaf Management, KUA.